(untitled) (Sains Humanika, 2018)
This study aims to evaluate the effectiveness of teaching aids (ABM) â€˜Pasang BongkarÂ Rak Alat Tulisâ€™ in stimulating the psychomotor of slow-learning students level 3 and level 4.This ABM is built to help the teaching and learning process (PdP) students with special needs in Manipulative Skills subjects especially for slow learner in raising student psychomotor stimulate. Qualitative approaches were used to obtain the study data through two instruments: observation and interview. The data collection process involves 16 students level 3 and level 4 for the special education stream as a sample to obtain data through observation, three (3) respondents with knowledge and expertise related to the Manipulative Skill subjects for the interview sessions. Data were analysed using content analysis method. The findings show that the ABM â€˜Pasang BongkarÂ Rak Alat Tulisâ€™ will help students with learning disabilities in Teaching and Learning Facilitation (PdPc) in the classroom. This can be proved by the students excitedly and more eager to include the components of the stationery rack back to the original shape. This can stimulate psychomotor students learning problem. Indirectly can stimulate student’s cognitive (thinking) and affective (attitude and values) to think how ABM can be reentered correctly. The conclusions from this study suggest that ABM can help to increase student psychomotor stimulation by installing and unloading methods practiced in this ABM. The implication of the study shows that the use of ABM â€˜Pasang BongkarÂ Rak Alat Tulisâ€™ is able to increase interest in PdP in the classroom and enhance the psychomotor capabilities of slow learner students.